PEMANFAATAN ABU TERBANG DAN ABU BATU STONE CRUSHER SEBAGAI FILLER PADA LAPIS BETON SEMEN PONDASI BAWAH (CEMENT TREATED SUBBASE/CTSB) - Yasruddin Yasruddin; Fauzi Rahman; Ayu Kumala Sari (Universitas Lambung Mangkurat, 2017)
Subbase course is a part of pavement courses between the base course and subgrade. The types of subbase course commonly used in Indonesia include: using good aggregate gradation and Cement Treated Base stabilization, Lime Treated Base stabilization, Soil Cement Stabilization and soil stabilization with lime (Soil Lime Stabilization). In the General Specification 2010 of the Ministry of Public Works of the Directorate General of Highways, aggregate stabilization with cement in the subbase course is called Cement Treated Subbase (CTSB). This CTSB has specifications with aggregate compositions which must meet the requirements in the sieve analysis specification: 95 - 100% pass the sieve in 1½ inche; 50 - 100% pass the sieve in ¾ inche; 20 - 60% pass the sieve of number 8 and 0 - 15% pass the sieve of number 200. The minimum compressive strength at 28 days should not be less than 75 kg/cm2 (7.5MPa). This research use fly ash and stone ash of stone crusher as filler which passing sieve number 200. The research begins with mortar research by varying the content of fly ash and stone ash of stone crusher by 0%, 5%, 10% and 15%. Mortar compressive strength was tested at age 3, 7, 14, 21, and 28 days. In this mortar research sought the largest compressive strength (optimum) to be continued to concrete research. The planned compressive concrete strength of 7.5MPa is tested at 28 days. Optimum mortar compressive strength was found on fly ash filler 10% age 28 day equal to 23.4MPa, stone ash of stone crusher filler 5% age 28 day equal to 17.21MPa and normal filler 0% age 28 day equal to 25.0MPa. As for compressive strength for CTSB normal concrete the average value is 13.49MPa, CTSB fly ash concrete 10% the average value is 14,72MPa and CTSB stone ash of stone crusher concrete 5% the average value is 11,80MPa at age 28 days. CTSB concrete strength test results in accordance with the General Specification 2010 of the Ministry of Public Works of Directorate General of Highways with a minimum compressive strength of 7.5MPa. Based on the result of concrete testing, fly ash and stone ash of stone crusher as filler can be used for CTSB (Cement Treated Subbase).